2007
DOI: 10.1590/s1517-86922007000400008
|View full text |Cite
|
Sign up to set email alerts
|

Lesões em surfistas profissionais

Abstract: The aim of this study was to verify the occurrence of injuries in Brazilian professional surfers who took part in one of the stages of the Professional Brazilian Surf Championship for men. There were 32 professional surfers participating in the study and each one of them filled in a questionnaire about the injuries they had suffered during the surf practice. There were found 112 injuries among all the participants of the study. Lacerations/cuts was the most frequent injury, 38 (33.9%); followed by sprains, 29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
3
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 14 publications
1
19
3
10
Order By: Relevance
“…To determine the sample, calculation was performed assuming 95% confidence, a sampling error of 3% and the proportion of surfers in the Brazilian population, which according to Base et al, 3 is 2.7 million. The proportion of surfers was calculated based on the Brazilian population size in 2007, which according to IBGE is 183.9 million inhabitants, resulting in 1.47%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the sample, calculation was performed assuming 95% confidence, a sampling error of 3% and the proportion of surfers in the Brazilian population, which according to Base et al, 3 is 2.7 million. The proportion of surfers was calculated based on the Brazilian population size in 2007, which according to IBGE is 183.9 million inhabitants, resulting in 1.47%.…”
Section: Methodsmentioning
confidence: 99%
“…In 2004, the number of surfers in the United States was estimated at 2.1 million 2 . In Brazil, nowadays is estimated 2.7 million, and according to the International Surfing Association the total number of practitioners of this sport in the world is 17 million 3 . In Brazil, the sport began to gain popularity in the early 60's, and due to the huge and appropriate country's coastline for its practice, with over 4,000 km long, the Brazilian surfers started to attain a level of recognition on the international competition scenario, both amateur and profissionals 4 …”
Section: Introductionmentioning
confidence: 99%
“…Although the literature contemplates studies on the physiological adaptations induced by the practice of surf [12][13][14][15] and the injuries and the risk of its practice [16][17][18][19] and indicate that the image of the surfer is increasingly linked to aspects of quality of life 20 , the fact that not many studies related to the subject in question were found prevented more comparisons with the findings to be made.…”
Section: Discussionmentioning
confidence: 99%
“…For the sample calculation, we considered the percentage of surfers was 1.47% 13,14 (2,803,770) of the total of the population in Brazil (190.732.694), according to data from the last Census/IBGE 2010. When adopting these parameters, based on the equation of a previous study 14 , the result was 62 surfers, and 66 were selected (figure 1).…”
Section: Methodsmentioning
confidence: 99%